2007
DOI: 10.1002/jbm.a.31441
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of hydrogels prepared from copolymerization of the different degrees of methacrylate‐grafted chondroitin sulfate macromers and acrylic acid

Abstract: Different degrees (between 20 and 75%) of methacrylate-grafted chondroitin sulfate (CS-MA) were synthesized. These CS-MA macromers were further copolymerized with acrylic acid (AA) at the molar ratio of 1 to 5 to form hydrogels. The sol percents of these CS-MA-AA hydrogels decreased and the cross-linking densities were studied with respect to the degrees of MA substitution onto CS-MA. The cytotoxicity with the increase in degree of MA substitution (DS) onto CS-MA as well as their hydrogels prepared from the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 30 publications
(30 reference statements)
1
6
0
Order By: Relevance
“…50 Thus, the degradation activity of chondroitinase is reduced by steric hindrance around cleavage sites. 51,52 Due to the steric hindrance by an increased density of catechol groups on the CS backbone, chondroitinase-mediated degradation seemed to be hampered in the 10× CS-CA hydrogels (Figure 1f).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…50 Thus, the degradation activity of chondroitinase is reduced by steric hindrance around cleavage sites. 51,52 Due to the steric hindrance by an increased density of catechol groups on the CS backbone, chondroitinase-mediated degradation seemed to be hampered in the 10× CS-CA hydrogels (Figure 1f).…”
Section: Resultsmentioning
confidence: 99%
“…During CS degradation by chondroitinase, β-elimination occurs on cleavage sites by neutralizing the charge on the carboxyl group of the uronic acid, abstracting the proton from the C-5 carbon, and releasing a 4-linked hexosamine with the generation of an unsaturated 4,5-bond on the uronic acid . Thus, the degradation activity of chondroitinase is reduced by steric hindrance around cleavage sites. , Due to the steric hindrance by an increased density of catechol groups on the CS backbone, chondroitinase-mediated degradation seemed to be hampered in the 10× CS-CA hydrogels (Figure f).…”
Section: Resultsmentioning
confidence: 99%
“…No publications examined the swelling characteristics over time of hydrogels solely based on CS­(G)­MA. However, swelling studies were reported on hydrogels based on CS­(G)­MA combined with other polymers like polyethylene glycol diacrylate. ,,, The hydrolytic stability of other MA ester-coupled polysaccharides as soluble polysaccharides and polymeric networks has previously been investigated. , MA-esters derivatized onto dextrans were previously found to only degrade as free polysaccharides but not in their cross-linked states. This difference in ester stability is attributed to the hydrophobic groups present in the polymerized MA backbone of the cross-linked network.…”
Section: Resultsmentioning
confidence: 99%
“…However, swelling studies were reported on hydrogels based on CS(G)MA combined with other polymers like polyethylene glycol diacrylate. 8,9,26,27 The hydrolytic stability of other MA ester-coupled polysaccharides as soluble polysaccharides and polymeric networks has previously been investigated. 22,23 MAesters derivatized onto dextrans were previously found to only degrade as free polysaccharides but not in their cross-linked states.…”
Section: Determination Of Methacrylate Hydrolysismentioning
confidence: 99%
“…If the cross peak 'α' is located at the position of some hydrogen peaks, they indicated that the peaks of H 1 , designated as geminal, and H 2 diagonal to H 3 had coupled to the H 3 hydrogen atom. [22][23][24] Next we measured the ratio of peak areas of geminal hydrogen and sum of the peaks of cis and trans hydrogens to verify the existence of the acrylate end group. The symmetry of acrylate end group was destroyed by the attachment of a carbonyl group (C=O) to the acrylate double bond, and three different hydrogen atoms were observed such as H 1 , H 2 and H 3 .…”
Section: Resultsmentioning
confidence: 99%